HUBUNGAN JENIS KEPRIBADIAN (EKSTROVERT & INTROVERT) DENGAN PENGUNGKAPAN DIRI (SELF DISCLOSURE) PADA PENGGUNA MEDIA SOSIAL INSTAGRAM: STUDI KASUS PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS TEKNOLOGI SUMBAWA - Wafiq Zuhair Muhammad; Yossy Dwi Erliana; Lukmanul Hakim (JURNAL PSIMAWA, 2021)
Self-dislcosure is an important part of a communication or relationship. Along with the development technology, self-disclosurehave been  used in various social media platforms, one of which is Instagram. Instagram makes it possible for someone to send photos and symbolic representation of their sensory and emotional experiences. This research aims to find the relationship of personality types with self-disclosure on Instagram users. Research is conducted on the Faculty of Psychology, Sumbawa University of Technology using a descriptive quantitative method. Data retrieval techniques using purposive sampling techniques with slovin formula. The sample is seventy one students. Data is obtained with a self- disclosure scale instrument based on the Eysenck’s theory and personality scales based on Jung’s theory. Hypothesis testing is carried out uses multiple trials. The results shows that there is a moderate and significant positive correlation between types of personality and self-disclosure to Instagram social media users of the Faculty of Psychology students at Sumbawa University of Technology with correlation coefficient value of r = 0.467 ; p= 0,000 or p < 0.05, which indicates that extrovert and introvert is simultaneously and significantly related to self disclosure on Instagramusers. Correlation between extrovert (X1) towards self-disclosure (Y) 0,000 < 0,05 with correlation coefficient value of 0,0467 indicates a positive correlation between extrovert and self-disclosure, while the correlation between introvert (X2) towards self-disclosure (Y) 0,384 < 0,05 with correlation coefficient value  of 0,105 which indicates that there is no correlation between introvert and self-disclosure. Based on this research, it stated that the more extroverted students, the higher self- disclosure on social media Instagram.